Rincón de arte y su influencia en el desarrollo creativo en niños de Educación Inicial II - Armijo Bravo, Nayeli Denisse (2024)
This study focuses on providing a perspective on the importance of improving education in the creative field of children, in which its main objective is to determine the influence of the Art Corner on the creative development in children of Initial Education II of the Unit “Juan León Mera” Educational Center in the Montalvo canton, Los Ríos province, the following investigation shows that the classrooms of the aforementioned institution lack learning corners such as the art corner, which is a fundamental resource for developing creativity and the skills of children. Creative development in children is essential for their comprehensive growth as it provides them with the skills and mentality necessary to adapt, innovate and encourage critical thinking. The methodology that was implemented in this research was the mixed approach that has the qualitative and quantitative method, applying a survey with closed questions that was carried out to classroom teachers and parents, allowing the result that there is misuse. of the art corner that did not allow the children's skills and creativity to easily develop. In conclusion, with this research it was diagnosed that the physical spaces of the art corner in that institution are not a space that satisfies the learning needs and do not have sufficient materials to meet educational expectations.